2018
DOI: 10.31788/rjc.2018.1122097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Compounds and Immunostimulatory Properties of Curcuma Mangga Rhizomes on Male Mice

Abstract: The current study was carried out to determine the constituents in ethanol extract of Curcuma mangga rhizomes and its immunostimulatory effects of the extract on cellular and humoral immunity of male mice. Determination of constituents in the extract was conducted using Ultra Performance Liquid Chromatography. The ethanol extract of Curcuma mangga was comprised to delayed-type hypersensitivity response and haemagglutinating antibody titre tests for its immunostimulatory potential. The test animal received extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The amount of quercetin in fermented A. cepa var aggregatum extract was higher after fermentation. Increase in quercetin content in fermented A. cepa var aggregatum was in accordance with previous studies (32,33). This might be due to flavonoid pathway such as glycosylation, deglycosylation, ring termination, methylation, glucuronidation, and sulfoconjugation, which were facilitated by microorganisms (32).…”
Section: Discussionsupporting
confidence: 91%
“…The amount of quercetin in fermented A. cepa var aggregatum extract was higher after fermentation. Increase in quercetin content in fermented A. cepa var aggregatum was in accordance with previous studies (32,33). This might be due to flavonoid pathway such as glycosylation, deglycosylation, ring termination, methylation, glucuronidation, and sulfoconjugation, which were facilitated by microorganisms (32).…”
Section: Discussionsupporting
confidence: 91%
“…Safety assessment revealed that it was untoxic in show short-term treatment 15 . The previous study has also shown the immunomodulatory properties of C. mangga 16 . However, the correlation between phytochemical constituents and its immunomodulatory activity was seldom reported.…”
Section: Introductionmentioning
confidence: 83%
“…It was found to have a variety of active secondary metabolites, such as flavonoids, saponins, glycosides, terpenoids, and steroids ( 11 ). Our previous study has displayed the immunomodulatory activities of C. mangga on phagocytosis, as well as delayed type hypersensitivity reaction and titer antibody by in vivo study in bovine-red blood cells challenged-rats ( 11 12 ). C. mangga has also been evaluated for its toxic effect which revealed that its LD50 was more than 5000 mg/kg BW, indicating that it was nontoxic ( 13 ).…”
Section: Introductionmentioning
confidence: 99%